Participatory monitoring for water management: a bibliometric analysis - Gloria Yaneth Flórez-Yepes; Mariana Escobar-Osorio; José Miguel Bermúdez-Piedrahita; Andrea Vaca-López (Dyna)
Communities play a central role in participatory water monitoring by contributing their local knowledge, engaging in data collection, and participating in decision-making related to the management and implementation of solutions. A systematic review was carried out in four phases under the PRISMA methodology. In phase 1, the study topic was defined. Phase 2 involved defining guiding questions and searching databases such as Scopus, Scielo, and Google Scholar. In phase 3, eligibility criteria and the search equation were established. Finally, in phase 4, review articles were selected, and the information was processed using VOSviewer software, followed by qualitative and quantitative analyses. Finally, it was determined that the studies conducted by various authors do not present participatory monitoring methodologies that are easy and affordable to apply in all community contexts. Each context must be analyzed individually. Additionally, most studies indicate that parameter measurements are not conducted in situ, highlighting a research gap in the application of participatory monitoring.